HUBUNGAN PENGETAHUAN IBU TENTANG PERAWATAN PAYUDARA DENGAN KESIAPAN MENGHADAPI MASA LAKTASI PADA IBU HAMIL DI PUSKESMAS MUTIARA BARAT TAHUN 2022 - Zaitun; Salamah; Ajirna Dewi (Nusantara Hasana Journal, 2022)
Breastfeeding is the process of giving breast milk (ASI) to babies. Giving breast milk (ASI) to babies is very beneficial for the growth and development of babies, especially giving the first milk which is yellowish in color (colostrum). This study aims to determine the relationship between mother's knowledge about breast care and readiness to face lactation in pregnant women at the Mutiara Barat Health Center, Pidie District. The research design used was analytic with a cross sectional design. The population in this study were all third trimester pregnant women with gestational age >28 weeks and a sample of 31 people. This research was conducted at the Mutiara Barat Health Center, Pidie District. Data were analyzed by Chi Square test with α=0.05. Data was collected by distributing questionnaires, then the data was processed with the help of a computerized system. The results showed that there was a relationship between mother's knowledge about breast care and readiness to face lactation at the Mutiara Barat Health Center, Pidie Regency. From the results of the Chi Square Test Statistics, at the significance level (α) = 0.05 it shows that the P Value = 0.000. Where (p < 0.05; significant), so it can be concluded that H0 is rejected, which means there is a relationship between mother's knowledge about breast care and readiness for lactation at the Mutiara Barat Health Center, Pidie Regency.